2014
DOI: 10.1128/jvi.01225-14
|View full text |Cite
|
Sign up to set email alerts
|

A Monomeric Uncleaved Respiratory Syncytial Virus F Antigen Retains Prefusion-Specific Neutralizing Epitopes

Abstract: Respiratory syncytial virus (RSV) is the leading infectious cause of severe respiratory disease in infants and a major cause of respiratory illness in the elderly. There remains an unmet vaccine need despite decades of research. Insufficient potency, homogeneity, and stability of previous RSV fusion protein (F) subunit vaccine candidates have hampered vaccine development. RSV F and related parainfluenza virus (PIV) F proteins are cleaved by furin during intracellular maturation, producing disulfide-linked F1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 21 publications
3
40
0
Order By: Relevance
“…As a result, the FP remains attached to the C terminus of F2, preventing a structural translocation of approximately 100 Å that would normally be required for the formation of the post-F 6HB. In line with results obtained by others, the removal of pep27 allowed the folding of the protein in its trimeric form (42,44,54). We have shown that the presence of pep27 and the two furin sites in the context of the Post-F-XC construct did not necessarily lead to a complete processing of the peptide.…”
Section: Discussionsupporting
confidence: 74%
“…As a result, the FP remains attached to the C terminus of F2, preventing a structural translocation of approximately 100 Å that would normally be required for the formation of the post-F 6HB. In line with results obtained by others, the removal of pep27 allowed the folding of the protein in its trimeric form (42,44,54). We have shown that the presence of pep27 and the two furin sites in the context of the Post-F-XC construct did not necessarily lead to a complete processing of the peptide.…”
Section: Discussionsupporting
confidence: 74%
“…As motavizumab has been previously shown to bind both cleaved and uncleaved RSV F with similar dissociation constants, quantification of cell surface expression should not be directly affected by processing (18). This experiment was also duplicated and confirmed with 18B2 (Argene), which targets an unknown epitope on F 1 that is exposed in both the pre-and postfusion forms (data not shown).…”
Section: Fig 2 Expression and Processing Of Hrc Mutations Transientlsupporting
confidence: 63%
“…Changes to the HRC (aa 75 to 97) region could be expected to affect processing as it is located N-terminal to the first cleavage site between amino acids 109 and 110. While there are currently no crystal structures of RSV F in its uncleaved state, it has previously been shown that the F protein is likely monomeric prior to cleavage and p27 removal (18,27). Changes in side chain packing may alter helical positioning within monomeric F, thereby affecting presentation of cleavage sites to the required protease(s).…”
Section: Discussionmentioning
confidence: 99%
“…Most recent RSV vaccine development efforts are focused on the F protein, which is relatively conserved among strains (3) and can be expressed in mammalian and insect cells (14,18,19,41). The G attachment protein, expressed on the virus surface, also represents an important target of protective immunity.…”
Section: Discussionmentioning
confidence: 99%
“…A mixture of F, G, and M recombinant proteins was tested in individuals Ͼ65 years old and was found to induce Ͼ4-fold increases in serum neutralizing activity in 58% of subjects with low prevaccine titers (16). Recently, the structures of the F protective targets recognized by the monoclonal antibodies (MAbs) palivizumab and 101F were resolved, as well as the prefusion form of the F protein trimer, leading to the structure-based design of stabilized F protein vaccine candidates (17)(18)(19). The G protein was also evaluated as a vaccine candidate in preclinical studies.…”
Section: Importancementioning
confidence: 99%